Preparation of thin-sections of painting fragments: Classical and innovative strategies - Pouyet, Emeline; Lluveras-Tenorio, Anna; Nevin, Austin; Saviello, Daniela; Sette, Francesco; Cotte, Marine (Analytica chimica acta, 2014)
[Display omitted] •New methods for the preparation of thin sections from painting fragment, in particular for FTIR microscopy.•SES method: embedding-free approach, suitable for the preparation of fresh or rich-binder paintings.•ARE method: use of an AgCl barrier coating to prevent the penetration/contamination of embedding resin.•Application to real cases: a deeper insight into ancient manufacturing or degradation processes of historical artefacts. For more than a century, the analyses of painting fragments have been carried out mainly through the preparation of thick resin-embedded cross-sections. Taking into account the development of innovative micro-analytical imaging techniques, alternatives to this standard preparation method are considered. Consequently, dedicated efforts are required to develop preparation protocols limiting the risks of chemical interferences (solubilisation, reduction/oxidation or other reactions) which modify the sample during its preparation, as well as the risks of analytical interferences (overlap of detected signals coming from the sample and from materials used in the preparation). This study focuses particularly on the preparation of thin-sections (1–20μm) for single or combined fourier transform infrared (FTIR) spectroscopy and X-ray 2D micro-analysis. A few strategies specially developed for the μFTIR analysis of painting cross-sections have already been reported and their potential extrapolation to the preparation of thin-sections is discussed. In addition, we propose two new specific methods: (i) the first is based on a free-embedding approach, ensuring a complete chemical and analytical neutrality. It is illustrated through application on polymeric design objects corpus; (ii) the second is based on a barrier coating approach which strengthens the sample and avoids the penetration of the resin into the sample. The barrier coating investigated is a silver chloride salt, an infrared transparent material, which remains malleable and soft after pellet compression, enabling microtoming. This last method was successfully applied to the preparation of a fragment from a gilded Chinese sculpture (15th C.) and was used to unravel a unique complex stratigraphy when combining μFTIR and μXRF.